PANDANGAN HIDUP MOHAMMAD HATTA SEBAGAI FALSAFAH PENDIDIKAN ISLAM DI INDONESIA - Ahmad Syauqi Fuady (Jurnal Pendidikan Agama Islam, 2025)
The aim of this article is to explain Mohammad Hatta's worldviev about God, the universe, humans, science, and society as the philosophy of Islamic education in Indonesia. First, God for Mohammad Hatta is the Creator and the Almighty. The form of human trust in God is faith and good deeds. Second, the universe is God's creation. The universe was created by God for humans to be used and managed with their knowledge. Third, Mohammad Hatta assessed that humans were created with two main responsibilities of worship and caliphate. Humans in this world are obliged to seek provisions for eternal life in the hereafter. Fourth, knowledge for Mohammad Hatta is not separate from religion. Both are equally important, although they have different methods and approaches. Fifth, regarding the people, Mohammad Hatta views that humans are individual beings who are social in nature. Individual human rights are respected by trying to form a society that helps each other, brotherhood, and deliberation.